Antifungal activity of seven essential oils against storage fungi Aspergillus flavus - Pandey , Ravindra Kumar (Journal of Postharvest Technology, 2022)
Several fungi cause diseases in crop plants. Of these some fungi predominates in agricultural produce during post-harvest storage. Storage fungi can grow at very low moisture range. During storage they produce certain toxic metabolites in the form of mycotoxins in the stored commodities making them unfit for human consumption. Aflatoxin is a mycotoxin produced by Aspergillus flavus, which is carcinogenic. Chemical fungicides are generally used to control the plant diseases. However these fungicides have deleterious effects on human and environment. Alternative sources of fungicides are being searched world over. The present study shows the inhibitory effect of seven essential oils Ajwain, Orange, Deodar, Dalchini, Guava, Jaifal and Clove against Aspergillus flavus. Mycelial growth inhibition assay was conducted to test the efficacy of essential oils. Growth inhibition studies showed that Ajwain, Dalchini, Clove, Jaifal and Deodar oils were found to be very effective against the test fungus. However Orange and Guava oil were not effective against the fungus.